Optimization of Empty Fruit Bunch Application to Improve Soil Organic Carbon, Total Soil Nitrogen, Earthworm Populations, and Oil Palm Performance on Spodosols - Adhy Ardiyanto; Suria Darma Tarigan; Rahayu Widyastuti; Budi Nugroho; Fathan Aldi Rivai (Universitas Sebelas Maret, 2026)
Using oil palm empty fruit bunches (EFB) as an organic amendment is a crucial strategy to improve soil quality in oil palm plantations, particularly on nutrient-poor Spodosol soils. This study aimed to evaluate the effects of 2 EFB application methods (incorporation into the soil and surface mulching) on soil organic carbon (SOC), nitrogen content, earthworm populations as soil biological indicators of fertility, and oil palm performance. A 12-month field experiment was conducted with observations every 4 months, using a completely randomized design (CRD) with 3 treatments and 9 replications each (n = 27 experimental units). The treatments included no EFB application (T0), EFB incorporated into the soil (T1), and EFB applied as surface mulch (T2). The results showed that both EFB application methods significantly increased SOC compared to the control, with the highest SOC observed in T2 (2.30±0.34%) after 12 months. Earthworm populations also increased progressively, reaching 19.33 individuals m-2 in T2. Pearson correlation analysis revealed a strong positive relationship between SOC content and earthworm abundance (r = 0.60; p < 0.001). These results confirm that EFB application, especially through surface mulching, is an effective and sustainable approach to enhancing soil quality, biological activity, and ecosystem functioning on Spodosols in oil palm plantations.